2023
DOI: 10.1039/d2cp05188e
|View full text |Cite|
|
Sign up to set email alerts
|

Structure effects of Pt15 clusters for the oxygen reduction reaction: first-principles calculations

Abstract: In the present work, the lowest energy structures and electronic properties of Pt15 clusters are investigated using first-principles calculations. The catalytic activity for the oxygen reduction reaction is analyzed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
1
6
1
Order By: Relevance
“…For example, we have recently found a new most stable structure for Pt 15 with a capped pyramid-like structure by performing simulated annealing based on molecular dynamics simulations. 24 The structure of this isomer is different to those of previously reported putative global minima. By means of a GA algorithm and the TPSS functional, we computed herein other low-lying isomer for Pt 15 ( 15.2 ) which is only 1.6 kcal mol −1 above the global minimum 15.1 reported in our previous work.…”
Section: Resultscontrasting
confidence: 86%
See 4 more Smart Citations
“…For example, we have recently found a new most stable structure for Pt 15 with a capped pyramid-like structure by performing simulated annealing based on molecular dynamics simulations. 24 The structure of this isomer is different to those of previously reported putative global minima. By means of a GA algorithm and the TPSS functional, we computed herein other low-lying isomer for Pt 15 ( 15.2 ) which is only 1.6 kcal mol −1 above the global minimum 15.1 reported in our previous work.…”
Section: Resultscontrasting
confidence: 86%
“…By means of a GA algorithm and the TPSS functional, we computed herein other low-lying isomer for Pt 15 ( 15.2 ) which is only 1.6 kcal mol −1 above the global minimum 15.1 reported in our previous work. 24 Moreover, we found that the structure of 15.2 is close to that put forward by Kumar et al 10 ( 15.3 ). The difference between the configurations of 15.2 and 15.3 lies in the position of a single Pt atom at the bottom of the structures shown in Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations